Talant, odaryonnost i sposobnost v strukture sportivnoj deyatelnost - Salnikov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The high and growing level of achievements in various kinds of sports is connected with the perfection of the control system in a training process. However the parameters on which it is carried out, vary in a due course. The opportunity of the achievement of outstanding results was contacted an intensification of processes of the training, the last years, but now it is contacted with the optimization of various components of the training process on the background of the maximal realization of individual reserves at various stages of a long-term training process. The acknowledgement of that specific features are taken into account obviously insufficiently. That is why many capable athletes have already left or are leaving sports appreciably not having opened their abilities because of that the standard system of training which is not taking into account their individual, mental features, functional and adaptable reserves was applied to them. There are the data at the same time, that very many of those who has achieved the results of the world level already being the adult,did not at all show endowments in the childhood.